Sentence Fragments in the Narration of the Novel "The Hunger Games" - Farhani Nurhusna (Lexicon, 2012)
The use of sentence fragments is generally discouraged in good English writing because they lack one or more essential components of a sentence, namely a subject and/or a predicate, and thus are grammatically unacceptable. However in fiction writing, the use of sentence fragments is not only quite common in dialogue, but in narration as well. The present study analyses sentence fragments in the narration of the first novel of the young-adult science-fiction trilogy The Hunger Games written by Suzanne Collins, to investigate the types of fragments employed in the novel and their classification based on syntactic structure in the form of dependent-clause fragments and phrase fragments. The sentence fragments were further analysed for their use based on the context of their preceding sentences. The use of sentence fragments in the novel basically serves the function of creating emphasis or stressing important points in the story.